Third-Person Imitation Learning via Image Difference and Variational Discriminator Bottleneck (Student Abstract) - Jiang, Chong; Zhang, Zongzhang; Chen, Zixuan; Zhu, Jiacheng; Jiang, Junpeng (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Third-person imitation learning (TPIL) is a variant of generative adversarial imitation learning and can learn an expert-like policy from third-person expert demonstrations. Third-person expert demonstrations usually exist in the form of videos recorded in a third-person perspective, and there is a lack of direct correspondence with samples generated by agent. To alleviate this problem, we improve TPIL by applying image difference and variational discriminator bottleneck. Empirically, our new method has better performance than TPIL on two MuJoCo tasks, Reacher and Inverted Pendulum.